Stroke Medicine Case Studies from Queen Square - Gill, S.K; Brown, M.M; Robertson, F.; Losseff, N. (Springer London : Imprint: Springer, 2015)
This collection of case studies is authored by a group of internationally recognised experts in the field of cerebrovascular disease. The cases are carefully selected to provide an insight into the different kinds of stroke syndromes from the common through to more rare presentations of cerebrovascular pathology. Each case is worked through with a discussion on presentation, clinical features, examination, radiological findings and management. Finally, learning points are highlighted to help the reader focus on the key points of the case study. Stroke Medicine: Case Studies from Queen Square is aimed at medical students and doctors in all stages of training from foundation years through to consultancy.